Utilizing bacteriophage to define the minimum residence time within a plug flow reactor. Issue 9 (11th March 2021) - Brown, Matthew R.; Orozco, Raquel
Abstract: As part of a viral mitigating strategy for continuous bioprocessing, that utilizes a plug flow reactor (PFR) for continuous viral inactivation (CVI), understanding the minimum residence time as a function of reactor scale and operational conditions is critical. An empirical‐based model was utilized to calculate the minimum duration a virus particle experiences within a plug flow reactor as a function of reactor design and operational conditions. This empirical model's calculations were challenged by pulse injecting the bacteriophage ΦX‐174 in non‐inactivating conditions and monitoring the discharge of the PFR with infectivity assays. The initial proposed empirical model, with the constraint of requiring an operational Dean number of >100, proved to be effective at calculating first breakthrough of ΦX‐174 but only for the appropriate Dean number conditions. With the knowledge gained from the first empirical model, a second was generated to eliminate the Dean number constraint. This second modified empirical model proved to be successful at calculating the first breakthrough at all Dean number's tested, however CVI operation at the lower Dean's number will lead to an increased asymmetry (i.e., increased tailing) in the residence time distribution. Abstract : In this study, the bacteriophage ΦX–174 was pulse injected into a 3‐D printed tubular reactor and flushed out. This discharge of the reactor was monitored for first breakthrough of ΦX–174 to identify the minimum residence time. These results were compared against an empirical model to determine the accuracy of the model to determine minimum residence time as a function of reactor pathlength, internal diameter, flow rate, and viscosity.